Exploring Concepts of the English-Language Tourism Advertising Discourse in Pre-Pandemic and Pandemic Times - Kolisnichenko, Tetiana; Osovska, Iryna; Tomniuk, Liudmyla (East European Journal of Psycholinguistics, 2022)
After the Second World War, 2019 definitely became one of the most significant strength tests for humanity that gave a boost to gradual but crucial changes in every person’s mental worldview models, which are particular deeply established constructs of reality. There is no sphere of activity that has not been affected by the coronavirus pandemic (COVID-19). Tourism became one of those areas most severely affected by the crisis, caused by pandemic conditions and quarantine measures. Consequently, they had to adjust to the new reality of life in circumstances of numerous human rights and freedom restrictions. This fact stipulates the topicality of the given comparative research. Based on the anthropocentric approach, the authors suggest the research methodology that lies in a complex approach to the discourse analysis as a platform for interrelations between the cognitive worldviews of addresser and addressee. Having identified the concepts-autochthons of the modern English-language tourism advertising discourse and determined their regular correlations, the cognitive map of the modern English-language tourism advertising discourse was designed. Having applied the comparative analysis of the cognitive maps of the traditional and modern English-language tourism advertising discourse, the authors determined the main suppositions of the English-speaking consumer of tourism services during pre-pandemic and pandemic periods. Thus, the traditional view of the English-speaking consumer of tourism services is the perception of tourism as the phenomenon related to unhindered, comfortable traveling and family holidays with gastronomic delight, new acquaintances and positive emotions. However, during the pandemic period, for English-speaking tourism services, consumer tourism became necessary for a change of surroundings, like a sip of fresh air that is available only by following quarantine rules and only in those countries open for tourists. Safety and sanitizing become the most critical factors in choosing a tourist location.
Keywords: COVID-19, tourism advertising discourse, conceptual system, cognitive map, domain, autochthon, concept